Sowing the Seeds for Rural Finance The Impact of Support Services for Credit Unions in Mexico - Bruhn, Miriam (The World Bank, 2018)
This paper studies the impact of a program that provides grants for technical assistance on the interest rates and outreach of credit unions in Mexico. Credit unions financing rural borrowers received grants in different years. The study uses propensity score matching and relies additionally on the timing of the grants to identify effects. The analysis shows that the program lowered lending interest rates by up to 2.6 percentage points (from a pre-program average of 17.8 percent). This drop appears to be due to lower operating costs and better risk management, as reflected in a lower nonperforming loan ratio. The program also raised credit unions' returns on assets and significantly increased the value of their loan portfolio